Overview of Dietary Diversity During the Complementary Feeding Period Using the Minimum Dietary Diversity Indicator - Marlia; Harleli (Journal of Epidemiology and Health Science, 2025)
Background: The first 1.000 days of life represent a critical window for a child's physical growth and cognitive development. Nutritional deficiencies or malnutrition during this period can result in stunted growth, impaired brain development, and reduced cognitive function, ultimately affecting a child's future potential. Adequate nutrition during early life is therefore essential to ensure optimal growth trajectories. One of the pivotal factors influencing toddler nutrition is the provision of appropriate complementary feeding, particularly for children aged 6–24 months. Among the various nutritional indicators, dietary diversity plays a fundamental role in achieving adequate nutrient intake and supporting healthy development. Objective: This study aims to assess dietary diversity during the complementary feeding period using the Minimum Dietary Diversity (MDD) indicator among children aged 6–24 months in Punggaloba Village, West Kendari District. Methods: This research employed a descriptive survey design involving 65 respondents, selected based on predetermined inclusion criteria. Data on complementary feeding practices and food intake patterns were collected and analyzed using univariate analysis to determine the prevalence of MDD compliance. Results: The study revealed that out of the 65 children assessed, the majority (78.46%) were in the 9–24 months age group. The proportion of children meeting the Minimum Dietary Diversity indicator was low, with only 19 children (29.2%) achieving the recommended dietary variety. The most commonly consumed foods during the complementary feeding period were rice, fish, eggs, and formula milk. Conversely, the consumption of vegetables and fruits remained inadequate, indicating limited dietary diversity among the study population. Conclusion: The findings underscore the urgent need to promote balanced and diverse complementary feeding practices in coastal communities, particularly in Punggaloba Village. Interventions focusing on nutrition education for caregivers are recommended to ensure sufficient nutrient intake and prevent malnutrition during this critical developmental period. Keywords: Dietary Diversity, Minimum Dietary Diversity, Complementary Feeding, Infant Nutrition, Child Health